STRUCTURE AND DEFECTS OF AN ORDERED ALUMINA FILM ON NIAL(110) - Libuda, Jörg; et al. (Surface Science, 1994)
Via oxidation a well ordered Al2O3 film may be grown on an ordered NiAl(110) surface. Its structure has been studied with SPA-LEED (spot-profile analysis) as well as with scanning tunneling microscopy (STM). The oxide overlayer grows strictly two-dimensional with a thickness of close to 5 Angstrom. Double diffraction spots have been observed but they are very weak, thus not excluding the existence of an interfacial layer between NiAl(110) and the oxide film. STM provides preliminary evidence for such a film and presents first clues to what the structure of the interface may be.The defect structure of the Al2O3 film has been investigated. In addition to boundaries between two rotational domains constituting the Al2O3 film, we also identify anti-phase domain boundaries through both the SPA-LEED as well as the STM measurements.